Evaluación de impacto ambiental y propuesta de un plan de manejo de residuos sólidos municipales, del área urbana del distrito de marcabal, sánchez carrión, la libertad. - López Alva, Giampier Walter (2015)
The purpose of this project was to evaluate the environmental impact generated by the current management of solid waste in urban district Marcabal and propose a management plan for them. The methodology used consists of four phases: the first conduct a situational analysis of the study area, the second was to conduct an environmental impact assessment (EIA) to the study area, the third was a study of characterization of solid waste and fourth phase was to propose a Plan of Solid Waste Management for the urban area of the District of Marcabal. The current situational analysis of the study area, is performed based on direct observation, conducting surveys and collecting information in the District. The identification and assessment of environmental impacts and their impact on environmental components, was performed by cause and effect matrices (Matrix Method Leopold), featuring columns level activities System Solid Waste Management and the row level environmental components: the aspects analyzed were: nature, extent, duration, reversibility, magnitude, importance, value and significance of impacts. Finally, a characterization is performed and a management plan for its Solid Waste was designed in order to seek an improvement in their current system of environmental management .